Pyruvate Carboxylase Deficiency Type C: A Rare Cause of Acute Transient Flaccid Paralysis with Ketoacidosis - Almomen, Momen; Sinclair, Graham; Stockler-Ipsiroglu, Sylvia G.; Horvath, Gabriella A. (Neuropediatrics, 2018)
Pyruvate carboxylase (PC) is a biotin-containing enzyme that is responsible for the adenosine triphosphate-dependent carboxylation of pyruvate to oxaloacetate, a key intermediate in the tricarboxylic acid cycle. PC deficiency (OMIM 266150) is a rare autosomal recessive metabolic disease, causing elevation of pyruvate, lactate, and alanine. Three types of PC deficiency have been described in the literature; A, B, and C. Type A PC deficiency, also called infantile or North American type, is characterized by infantile onset acidosis, failure to thrive, and developmental delay. The second subtype or type B, the neonatal or French form, presents usually in the neonatal period, mostly in the first 72 hours of life with severe lactic acidosis, truncal hypotonia, and seizures. The third type is called type C, is extremely rare with few cases published in the literature. In this case report, we present an 11-month-old girl who presented with acute flaccid paralysis, lethargy, and constipation with elevated ketones and lactate. She was confirmed genetically and biochemically to have PC deficiency type C. The patient's unusual presentation expands the clinical phenotype of this extremely rare disease.
Keywords: pyruvate carboxylase; flaccid paralysis; ketosis; lactic acidosis; hypotonia